(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
The study aimed to find out the impact of administrative empowerment with the dimensions of delegation of authority, motivating employees, decision-making, training, and effective communication on strategic success represented by survival, growth, and adaptation in the Jordanian Islamic banks. The sample included (357) employees, and the study relied on descriptive statistical analysis, regression analysis, and average differences analysis. The study found that the employees of Jordanian Islamic banks estimate the level of administrative empowerment on average; and they estimate the level of strategic success as high, and it showed that administrative empowerment has a positive and statistically significant effect on strategic success; in addition, in most cases, there was no statistically significant effect of motivating workers and decision-making on strategic success. Furthermore, it showed that there were no statistically significant differences between averages of administrative empowerment that can be attributed to any of the demographic variables. The study recommended Jordanian Islamic banks should raise the level of administrative empowerment because it has an impact on strategic success in the long term, they should improve the level of motivating employees, and give them a broader scope to participate in decision-making.